The effect of two challenge doses of Dictyocaulus filaria on the acquired immunity of sheep vaccinated with "Filiraq". - Al.Samarrae, S. A.G.; Hassan, S. A.K.; Latif, ,B. M.A. (The Iraqi Journal of Veterinary Medicine, 1999)
Twenty six lambs divided into four groups were used to study the effect of experimental infection with two challenge doses of D.filaria ( 100 & 300 larvae / Kg. B. W.) on the aquired immunity after vaccination with irradiated larval vaccine “ Filiraq”. The clinical symptoms , eosinophi lic response, blood picture, faecal larval counts, gross pathological changes & adult worm counts in the lungs were studied ... The results showed that a high dose of challenge (300 LI kg) prevents the development of expected acquired immunity, however the other vaccinated & challenged group ( 100 LI Kg B.W ) showed good level of acquired immunity in comparison with other group.